"The More Things Change, The More They Stay the Same": Path dependency, sports content, and the suppression of innovation in mobile television. Issue 2 (May 2016) - Hutchins, Brett
Abstract: This paper uses the concept of path dependency to analyse the suppression of mobile media innovation in commercial telecommunications markets. This process is discussed in relation to the case of Optus "TV Now" in Australia, a cloud-based mobile television service that was subject to successful legal action to prevent its operation. The service was found to infringe the intellectual property rights of two major football leagues and a powerful telecommunications incumbent, Telstra. The details of this case study highlight the concentration of market power in the Australian telecommunications sector, and the high level of strategic value placed upon sports content in the development and delivery of new mobile media services. The analysis presented is informed by semi-structured in-depth interviews with the representatives of industry and market regulators, technology commentators, and professionals working in the telecommunications industry, as well as legal documents related to the TV Now court proceedings and service.